Changes after 12 years of follow-up severe asthma patients cohort: higher obstruction and comorbidities, but significant better quality of life. (1st February 2023) - Santos Jr., N. G.; Lima, R. M.; Athanazio, R. A.; Carvalho Pinto, R. M.; Rabe, K.; Cukier, A.; Stelmach, R.
Abstract: Background: The Brazilian Cohort of Asthma São Paulo (BRASASP) had a well-characterized severe asthmatic in Brazil, with 12 years of follow-up under standard treatment. Methods: Sequential assessment of patients with uncontrolled asthma from BRASASP cohort was carried out with 12 years of follow-up, performing exams and comparing with previous measurements. Results: 50 from the 60 initial patients were reevaluated. Twelve years later, FEV1 and the FEV1/FVC ratio have significantly decreased, with a rate of loss of lung function of 11.8 and 14%, respectively, and worsening in small airway parameters such as RV/TLC. BMI, The Asthma Control Test (ACT) and Asthma Control Questionnaire (ACQ) scores haven't changed. However, exacerbations decreased by 56%. Mean daily inhaled corticosteroid use was similar over time, but daily oral corticosteroid use decreased, in addition to a significant reduction in induced sputum eosinophilic and neutrophilic profile and serum IgE. Rhinitis, sinusitis, and GERD were the main comorbidities. In quality of life according to respiratory questionnaire SGRQ, total score showed a huge improvement (62% of patients). Conclusions: There was significant decrease in FEV1 and FEV1/FVC. Data of pulmonary functional small airway characteristics show globally affected airways. Although higher doses of medications, patients were still uncontrolled, but with reduction of exacerbations, daily use of oral corticosteroid, less eosinophils and neutrophils in induced sputum and lower levels of IgE. Improvement in quality of life in 62% of patients.